2009
DOI: 10.1177/0269881109102779
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of antidepressant-associated sexual dysfunction in three European countries: replication in a cross-sectional patient survey

Abstract: Sexual dysfunction is a common but often unrecognized side effect of many antidepressants. Building upon the results of a previous investigation, this study aimed to assess the prevalence and impact of antidepressant-associated sexual dysfunction (AASD) in three European countries. A cross-sectional survey of 704 adults in Germany, Spain, and The Netherlands was used in the study. All participants had recently started taking a selective serotonin reuptake inhibitor or serotonin- noradrenaline reuptake inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 17 publications
2
63
0
4
Order By: Relevance
“…Two international studies of the prevalence of sexual dysfunction in depressed patients undergoing treatment with either an SSRI or serotonin-noradrenaline reuptake inhibitor (SNRI), which both accounted for self-reported sexual problems before starting treatment and the potential adverse effects of concomitant medication, found that 27-65% of female and 26-57% of male patients experienced either a worsening of pre-existing difficulties or the emergence of new sexual difficulties in the early weeks of treatment 65,66 .…”
Section: Influence Of Treatment Of Depression On Sexualitymentioning
confidence: 99%
“…Two international studies of the prevalence of sexual dysfunction in depressed patients undergoing treatment with either an SSRI or serotonin-noradrenaline reuptake inhibitor (SNRI), which both accounted for self-reported sexual problems before starting treatment and the potential adverse effects of concomitant medication, found that 27-65% of female and 26-57% of male patients experienced either a worsening of pre-existing difficulties or the emergence of new sexual difficulties in the early weeks of treatment 65,66 .…”
Section: Influence Of Treatment Of Depression On Sexualitymentioning
confidence: 99%
“…13 SD is one of the main reasons patients choose to discontinue SSRI treatment, and it can also cause poor adherence patterns among patients who choose to continue taking the medication. 4 In one study of patients with major depressive disorder, 85% of patients rated the management of sexual dysfunction as "extremely important," "very important," or "important."…”
Section: Impact Of Antidepressant-induced Sexual Side Effectsmentioning
confidence: 99%
“…(See Table I.) Nonetheless, the general consensus is, firstly, that there is a high incidence of sexual dysfunction attributable to SSRI and SNRI usagethe best estimate probably in the region of 30 to 50% -and that this is a dose-related class effect, 25 secondly, consensus is that drugs with different pharmacological actions are less inclined to affect sexual functioning.…”
Section: Antidepressant-induced Sexual Dysfunctionmentioning
confidence: 99%